2006
DOI: 10.1590/s1676-06032006000100002
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of the Refugial Hypothesis of Amazonian speciation: a paleoecological perspective

Abstract: The refugial hypothesis is treated as the definitive history of Amazonian forests in many texts. Surprisingly, this important theoretical framework has not been based on paleoecological data. Consequently, a model of Amazonian aridity during the northern hemispheric glaciation has been accepted uncritically. Ironically, the Refuge Hypothesis has not been tested by paleobotanical data. We present a revision of the concept of Neotropical Pleistocene Forest Refuges and test it in the light of paleocological studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
112
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 50 publications
5
112
0
8
Order By: Relevance
“…For many years the Pleistocene refuge hypothesis (Haffer, 1969;Vanzolini and Williams, 1970) was assumed to represent the principal mechanism to explain diversification in the Amazon basin and other lowland rainforest regions in South America (Carnaval and Moritz, 2008;Whitmore and Prance, 1987). However, not all paleoecological data supported the presence of the postulated non-forested barriers during the Pleistocene (Bush and de Oliveira, 2006;Colinvaux et al, 2000), and phylogenetic analyses indicated that most diversification events in this region predate the Pleistocene climatic oscillations (Hoorn et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…For many years the Pleistocene refuge hypothesis (Haffer, 1969;Vanzolini and Williams, 1970) was assumed to represent the principal mechanism to explain diversification in the Amazon basin and other lowland rainforest regions in South America (Carnaval and Moritz, 2008;Whitmore and Prance, 1987). However, not all paleoecological data supported the presence of the postulated non-forested barriers during the Pleistocene (Bush and de Oliveira, 2006;Colinvaux et al, 2000), and phylogenetic analyses indicated that most diversification events in this region predate the Pleistocene climatic oscillations (Hoorn et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…It is made up of a mixture of species that have evolved from native vegetation from the era in which South America was separating from Africa, 65 million years ago, with the original Ombrophylus dense forest cover. On the other hand, in the northeast and in the south, the Atlantic Forest expanded and retracted during the Quaternary (Brown Jr., 1987;Behling and Negrelle, 2001;Ledru et al, 2005;Bush and Oliveira, 2006). There is also abundant information about possible past connections between the Atlantic Forest and the more recent Forests of the Amazon Basin (Thomas et al, 1998;Costa, 2003) During the last 500 hundred years, the Atlantic Forest has been exploited and destroyed, being replaced first by sugarcane in the NE region (XVI century), and then later by coffee in Rio de Janeiro and São Paulo (XVIII and XIX century), by cattle ranching in São Paulo and Minas Gerais (XIX and XX century), by cocoa in Bahia (XX century), and more recently by Eucalyptus forest for cellulose and paper production.…”
Section: Introductionmentioning
confidence: 99%
“…These seasonally dry forests are areas of "ecological tension" between the Amazonian and Cerrado biomes and are bounded by the evergreen rain forests to the north and by savannas to the south. Seasonally dry forests, which provide optimum habitat for mahogany, probably expanded during the cool and dry glacial intervals (Pennington et al 2000;Bush and Silman, 2004;Bush and Oliveira, 2006;Colinvaux et al 1996Colinvaux et al , 2001) and mahogany population sizes would have been correspondingly larger and possibly more continuous in some areas. During the wetter and warmer Holocene, rainforests expanded south and eastwards replacing the deciduous forests and savannas The high level of private haplotype diversity found in the Marajoara population, in contrast to other Amazonian populations, suggests additional intricacy to the pattern.…”
mentioning
confidence: 99%